Price level targeting and risk management - Roberto Billi (Sveriges Riksbank, 2016)
Many argue that, because the outlook for the economy is uncertain, monetary policy should apply a risk management approach by raising the policy interest rate gradually from its lower bound. Using a small New Keynesian model, I study the impact of outlook uncertainty on the economic performance of a central bank with a target for the price level or the level of nominal gross domestic product. I show that, in the presence of persistent supply and demand shocks, a price-level target is more effective at mitigating outlook uncertainty because it induces greater policy inertia and improves the tradeo¤s faced by the central bank.
Keywords: E31; E52; E58; 330; nominal level targets; optimal policy; inertial Taylor rule